CHARACTERISTICS OF COGNITIVE ABILITY DEVELOPMENT OF STUDENTS AND PUPILS (Konferensiyalar | Conferences, 2024)
In the Republic of Kazakhstan, comprehensive development of cognitive ability of the future generation and pupils and students and creation of favorable conditions for it is of great importance. Also, in the Law of the Republic of Kazakhstan "On Education", one of the principles of state policy is "to encourage the qualification and talent of an individual". it is necessary to develop" - it is stated.